English-only or Home Language in Testing? Researching Preferences on Home Language Use in Language Assessment in Poland, Georgia and Brazil - Krajka, Jarosław (Papers in Linguistics, 2025)
Between the Grammar Translation Method favouring L1 use and Communicative Language Teaching refraining from it, language teachers have a range of options for the use of L1 and L2. While it is accepted that the target language should dominate instruction, this does not have to be the same in assessment. It is interesting to examine how teachers approach L1 and translation in testing, and how their socially rooted perceptions about testing coincide with their testing practices. The present study investigates the effect of teachers’ culture on their attitudes towards home language use in language assessment by a semi-closed questionnaire examining opinions of Polish, Georgian and Brazilian teachers. The undertaken research showed differences in testing habits across cultures; however, at the same time, the effect of globalized teaching methodology is also visible.